Penerapan Digital Marketing untuk UMKM di Desa Branta Tinggi Kecamatan Tlanakan Kabupaten Pamekasan - Rahman, Abd.; Farodis, Zian (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Real Work Lecture (KKN) activity aims to help develop Micro, Small and Medium Enterprises (MSMEs) in Branta Tinggi Village, Tlanakan, through implementing digital marketing strategies. MSMEs have an important role in the village economy, but are often less than optimal in utilizing digital technology to expand markets and increase sales. Therefore, the KKN team focuses on providing training and assistance to MSMEs regarding the use of social media, creating promotional content, and utilizing e-commerce platforms. The methods used include an initial survey to identify the needs of MSMEs, direct training, and evaluation of the success of implementing digital marketing strategies. The results of this activity show an increase in MSME actors' understanding of digital marketing and an increase in market reach and sales of their products. It is hoped that the application of digital marketing can continue to be developed to increase the competitiveness of MSMEs in Branta Tinggi Village.